Hypogammaglobulinemic sprue manifested as chronic intestinal failure: An uncommon but effective indication for home parenteral nutrition - Nunes, Gonçalo; Martins, Cláudio; Teixeira, Cristina; Fróis Borges, Miguel; Paula Oliveira, Ana; Fonseca, Jorge (Turkish Journal of Gastroenterology, 2018)
Abstract Cite this article as: Nunes G, Martins C, Teixeira C, Fróis-Borges M, Oliveira AP, Fonseca J. Hypogammaglobulinemic sprue manifested as chronic intestinal failure: An uncommon but effective indication for home parenteral nutrition. Turk J Gastroenterol 2018; 29: 717-8.